Openness to Experience and Creativity: The Role of Promotion Focus - Saliha Gul Abbasi; Mohammed Abdulrazzaq Alaghbari; Mazhar Abbas; Baligh Beshr; Basheer M. Al-Ghazali (Cogent Business & Management, 2023)
This paper investigates the impact of openness to experience (OE) on the two distinct dimensions of creativity; radical creativity (RC) and incremental creativity, with promotion focus (PF) as regulatory factor and as the mediating mechanism. Drawing on the recent re-conceptualization of creativity as a multi-dimensional phenomenon; the current study attempts to explain the relationship of OE and PF with two dimensions of creativity. Sample is drawn from employees of advertising agencies working in creative departments. A three wave time lagged survey of 293 creative employees of advertising agencies in Karachi, Pakistan was conducted. SPSS Process Macro and AMOS software were used to analyze the data. OE was found to have an impact on both dimensions of creativity, but mediation effects of PF were confirmed between OE and RC only. The findings may assist the managers to better plan, hire and manage their creative workforce according to the jobs that require different forms of creativity. Future directions and limitations are discussed following the findings.
Keywords: 650; Advertising; incremental creativity; openness to experience; Pakistan; promotion focus; radical creativity